Efficacy and Tolerability of Eight Antimicrobial Regimens in the Outpatient Treatment of Exacerbations of Chronic Obstructive Pulmonary Disease - Jordan Minov; Jovanka Karadzinska-Bislimovska; Tatjana Petrova; Kristin Vasilevska; Sasho Stoleski; Dragan Mijakoski; Snezana Risteska-Kuc (ID Design Press, 2014)
BACKGROUND: Bacterial infections are considered as the most important cause of exacerbations in patients with chronic obstructive pulmonary disease. AIM: To compare the efficacy and tolerability of eight antibiotics empirically administered for outpatient treatment of exacerbations of COPD. METHODS: We performed an observational study including 343 COPD patients with probable bacterial exacerbation (Group A and Group B COPD patients) managed in an outpatient setting. Eight antibiotic regimens each used 10 days were evaluated: amoxicillin/clavulonic acid, doxycycline, cefuroxime, cefixime, clarithromycin, roxithromycin, ciprofloxacin, and moxifloxacin. All patients were followed up for 30 days, with an intermediate visits at 5, 7 and 10 days at which the duration of symptoms and the side-effects of the drug were evaluated. RESULTS: The clinical success rate varied from 69.8% with doxycycline to 80.9% with moxifloxacin. The mean time to relief of symptoms varied from 5.6 days with moxifloxacin to 6.3 days with amoxicillin/clavulonic acid. Significant increase of the post-treatment FEV1 value was registered in all treatment groups. Relapse within the first 20 days was registered in the group receiving doxycycline, clarithromycin, and ciprofloxacin. The prevalence of the adverse events was low varying from 6.7% with cefuroxime to 11.3% with ciprofloxacin. CONCLUSION: Our findings suggest high clinical success rate and high safety of all studied regimens.
Keywords: adverse effect; antibiotic; Chronic obstructive pulmonary disease; Clinical success; Exacerbation